Mini-Incision Total Hip Replacement—Surgical Technique and Early Results - WK Chung; D Liu; LSS Foo (Journal of Orthopaedic Surgery, 2004)
Purpose. To compare the results of mini-incision total hip replacement (MITHR) to the standard posterior approach and evaluate the advantages and disadvantages of MITHR. Methods. 60 patients with osteoarthritis of the hip underwent total hip replacement utilising a mini-incision technique. They were compared to a matched cohort of patients who received the standard posterior approach. The average follow-up period was 14 months. The patients were compared with respect to the length of the incision, surgical time, intra-operative blood loss, narcotic requirements, length of hospital stay, requirement for walking aids, Harris hip score, and complications. Results. The length of the skin incision for MITHR, at an average of 9.2 cm, was half that of the standard approach. Statistically significant differences were found between the 2 groups in terms of intra-operative blood loss, length of hospital stay, and use of walking aids, all in favour of MITHR. There were no differences between the two approaches with regard to operating time, narcotic requirements, or Harris hip score. There were no cases of component malpositioning or major complications in the MITHR group. Conclusion. Uncemented total hip replacement can be effectively performed through a smaller incision utilising MITHR without increased risk of complications. Significant benefits include less intra-operative blood loss, shorter hospitalisation, and cosmesis.